PERANCANGAN SISTEM INFORMASI ABSENSI DAN PENGGAJIAN KARYAWAN DENGAN METODE FRAMEWORK LARAVEL DAN SCRUM PADA DANEZ HEALTH CARE - Anwar Tonggo Sitorus; Rinaldo, Rinaldo (Jurnal Teknik dan Science, 2023)
Danez Health Care is a pharmaceutical service facility that has been established since 2014 and now has 1 Clinic branch and 4 Pharmacy branches in Purwakarta, Bekasi and Bogor. Danez Health Care's head office is in the same location as its clinic, namely in Bogor. However, the attendance process that occurs at Danez Health Care is still done manually by each branch which makes it difficult for Finance / HRD to control working hours and calculate the net salary of employees at each branch. Seeing the existing problems and to make it easier for Finance/HRD to control employee working hours and attendance accuracy, a website-based employee attendance and payroll application is needed using the Laravel framework and scrum methodology. To produce salary calculations that are directly systemised on employee attendance data, it also makes it easier to collect attendance data. The design of the application uses UML design tools, balsamiq mockup, xampp and mysql as a database. The results of this study are in the form of an attendance application that can be directly connected to the calculation of employee net salaries every month, and can produce pay slips, employee absence recap data from all branches, calculation of employee net salaries that can provide information quickly to Finance/HRD.